Odpowiedź:
[tex]x= 2,96 \ 10^{8} m[/tex]
Wyjaśnienie:
m= masa rakiety
[tex]M_{z}[/tex]- masa Ziemi
[tex]M_{k}[/tex]- masa Księżyca
l- odległość Ziemia-Księżyc
x-odległość Ziemia-rakieta
[tex]M_{z}=81M_{k}\\l=vt= 3 \ 10^{8} \frac{m}{s} \ 1s = 3 \ 10^{8}m\\F_{gK}=G\frac{M_{k}m}{l-x} \\F_{gZ}=G\frac{M_{z}m}{x} \\\\\\F_{gK}=F_{gZ}\\G\frac{M_{k}m}{l-x} =G\frac{M_{z}m}{x} \\\frac{M_{k}}{l-x}=\frac{81M_{k}}{x}\\\frac{1}{l-x} =\frac{81}{x} \\x=81l-81x\\82x=81l\\x=\frac{81 \ 3 \ 10^{8}}{82} = 2,96 \ 10^{8} m[/tex]
Jeśli do wyniku dodać jeszcze promień Ziemi, zmiana będzie praktycznie niezauważalna.